A transformer free quadratic boost converter using synthesized switched inductor - Mohan D; Sreedevi V T (Results in Engineering)
This work presents a novel DC-DC high gain, transformer-less, modified QBC (Quadratic Boost Converter) for renewable energy applications. The suggested QBC topology is a reformed version of the conventional QBC with two switches using a synthesized switched inductor. Due to the topology modification, the suggested converter accomplishes a high gain of 16 from 24 V to 380 V at a duty ratio of 0.65, with a reduced voltage stress across the switches. These characteristics permit the proposed converter to operate efficiently at high voltage gains without requiring extreme duty cycle values, making it an excellent interface for renewable energy power generation systems.The working principle of the proposed topology is analysed in both continuous conduction mode (CCM) and discontinuous conduction mode (DCM) and the governing equations are presented. An experimental prototype of 200 W is implemented to verify the effectiveness of the proposed converter. The experimental results prove the superior performance of the suggested novel converter in comparison with the existing QBC topologies.